Patterns of contraceptive use in urban areas of Kohgiluyeh-Boyerahmad in 2004 - Goshtasebi, Azita; Vahdaninia, Maryam Sadat (Journal of Reproduction & Infertility, 2006)
Introduction: Achieving comprehensive reproductive health services, including family planning as the basis of family health and sexual health, has been internationally the main objective of governments and health policy makers in the past decades. Improving modern family planning facilities would lead to a promotion in population control. This study investigates family planning indices, its short comings and mean of reproductive variables in the urban areas of Kohgiluyeh-Boyerahmad province in comparison with the data from Demographic Health Survey carried out in Iran in 2000.Materials & Methods: Considering the high coverage of households by urban health centers in the province, 1540 married women were randomly selected from the list of names in each health center and they were interviewed during 2004. A researcher-devised questionnaire, (content validity determined by experts), was used consisting of demographic variables, family planning awareness status methods, the contraceptive method used by the couples and the number of a desired and live children. Using SPSS, version 13, the data were analyzed in a descriptive-analytical fashion with a significance level of 0.05.Results: The mean age of the respondents was 33.2+ 9.4 years. The mean numbers of pregnancies and children were 3.7 and 3.2 respectively. There was a significant relation between the mean number of children and women's educational status and job (p-value <0.001). A significant difference was also observed between the mean and the desired number of children (t=4.46, p-value <0.001). The most common family planning methods were OCP and TL (40.4% & 18.7% respectively). The highest knowledge about family planning methods was on OCP, condom and TL (94%, 65.4% & 45.2% respectively). Highest number of women with one child and women with ≥3 children were in the 21-30 and 31-40 age groups respectively. Conclusion: The findings indicate that family planning programs have had a relatively appropriate effectiveness on population control in Kohgiluyeh-Boyerahmad province and family dimension is relatively satisfactory but despite better knowledge about modern contraceptives, use of modern family planning methods is not desirable. Considering the high number of children by women from older age groups, the need for educating and promoting the use of modern contraceptives is still of importance.
Keywords: Family planning indices; Family planning; Women; Contraceptive method; Reproductive health; Kohgiluyeh-boyerahmad; Urban areas